Water saving under a developed microcontroller based automated drip irrigation system in Kinnow crop - DEBNATH, MANISH; PATEL, NEELAM; RAJPUT, T. B.S.; MONDAL, SANGEETA (Journal of Soil and Water Conservation, 2021)
Efficient utilization of available water resources is crucial for a country like, India, which shares 17% of the global population with only 2.4% of land and 4% of the water resources. More than 50% of water wastes in the conventional irrigation systems consequently resulting in to low irrigation efficiency at field level. Drip irrigation is though one of the best options for enhancing irrigation efficiency and crop yields per unit of water applied, it can be automated further using low cost sensors for irrigation automation. A microcontroller based sensor circuit to measure leaf-air temperature differential was developed in laboratory and was integrated with the drip head works for irrigation automation. Developed system was techno-economic evaluated in Kinnow and water saving as compared to other conventional irrigation systems was estimated. Soil moisture content, leaf-air temperature differential, crop canopy diameter, leaf area index were monitored during the study period. The system maintained soil moisture content nearer to the field capacity (30.02%) based on temperature differential values. The developed system uses 8.6% and 49.6% less water than to the manual operated drip irrigation system and check basin irrigation system, respectively.